Teacup - Young, Rebecca (Dial Books for Young Readers, 2016)
A boy must leave his home and find another. He brings with him a teacup full of earth from the place where he grew up, and sets off to sea. Some days, the journey is peaceful, and the skies are cloudless and bright. Some days, storms threaten to overturn his boat. And some days, the smallest amount of hope grows into something glorious. At last, the boy finds land, but it doesn't feel complete ... until another traveler joins him, bearing the seed to build a new home
Originally published in Australia 2015 by Scholastic Australia
Keywords: Migration; Reise; Selbstvertrauen; Flüchtlingskind; Boot; Voyages and travels / Juvenile fiction; Emigration and immigration / Juvenile fiction; Self-reliance in children / Juvenile fiction; Voyages and travels / Fiction; Emigration and immigration / Fiction; Self-reliance / Fiction; JUVENILE FICTION / Social Issues / Emigration & Immigration; JUVENILE FICTION / Social Issues / New Experience; JUVENILE FICTION / Social Issues / Self-Esteem & Self-Reliance; Emigration and immigration; Self-reliance in children; Voyages and travels; Immigration and emigration / Fiction; Picture books for children; Illustrated works; Fiction; Juvenile works; Picture books; Bilderbuch